Effectiveness of Penitentiary Institution to Prevent Recidivism Asimilation Cases in The Era of Pandemic COVID-19 - Yuliandhari, Savira Afra (Universitas Semarang, 2021)
In principle, all convicts undergo a period of guidance at the correctional institutions after a court decision is made. But in reality, the process of mentoring assisted residents based on the correctional system is hampered by existing problems such as overcapacity, budget or funding factors, lack of facilities and infrastructure to support coaching for all assisted residents and lack of enthusiasm for certain assisted members to carry out guidance. The type of research used is juridical empirical. So the focus in this research is the problems that faced by correctional institutions, it shows that the development process carried out by the correctional institutions is still running effectively, especially in terms of preventing the occurrence of recurrent crimes committed by inmates who get the right of covid-19 assimilation